Manifesting Bolaang Mongondow Local Wisdom Through the Creation of Sinungkudan Dance - Riana Diah Sitharesmi; Trubus Semiaji (Graduate School of Institut Seni Indonesia Yogyakarta, 2026)
This paper examines the manifestation of Bolaang Mongondow local wisdom in the creation of Sinungkudan dance as a contemporary reconstruction of the traditional Mosau’ dance. The study aims to explore how local cultural values can be revitalised through dance creativity while maintaining their philosophical and aesthetic roots. The research applies a qualitative approach through autoethnography and artistic-based research as research method, positioning the researchers as both cultural participants and artistic collaborators in the creative process. The data were collected through participatory observation, studio practice documentation, interviews, reflective journals, and performance recordings. The findings show that Sinungkudan transforms the movement motifs, symbolic properties, musical elements, and social meanings of Mosau’ into a new choreographic form that remain closely connected to Bolaang Mongondow cultural identity. The local wisdom manifested in the dance includes values of courage, kinship, resilience, collective solidarity, respect for women, and social harmony rooted in the Mogama tradition. Through contemporary presentation strategies familiar to younger generations, Sinungkudan functions not only as an artistic performance but also as a medium for cultural revitalisation and intergenerational transmission of local values. Manifestasi Nilai Lokal Bolaang Mongondow dalam Kreasi Tari Sinungkudan Abstrak Tulisan ini mengkaji manifestasi kearifan lokal Bolaang Mongondow dalam penciptaan tari Sinungkudan sebagai rekonstruksi kontemporer atas tari tradisional Mosau’. Kajian bertujuan untuk mengeksplorasi bagaimana nilai-nilai budaya lokal dapat dihidupkan kembali melalui kreativitas tari dengan tetap mempertahankan akar filosofis dan estetiknya. Penelitian menerapkan pendekatan kualitatif melalui autoetnografi dan penelitian berbasis seni sebagai metode riset, menempatkan para peneliti sebagai partisipan budaya dan kolaborator artistik dalam proses kreatif. Data dikumpulkan melalui observasi partisipatif, dokumentasi praktik studio, wawancara, jurnal reflektif, dan rekaman pertunjukan. Temuan menunjukkan bahwa Sinungkudan mentransformasikan motif gerakan, sifat simbolik, unsur musik, dan makna sosial Mosau’ menjadi bentuk koreografi baru yang tetap terhubung erat dengan identitas budaya Bolaang Mongondow. Kearifan lokal yang termanifestasi dalam tarian tersebut mencakup nilai-nilai keberanian, kekerabatan, ketahanan, solidaritas kolektif, penghormatan terhadap perempuan, dan harmoni sosial yang berakar pada tradisi Mogama. Melalui strategi presentasi kontemporer yang familiar bagi generasi muda, Sinungkudan berfungsi tidak hanya sebagai pertunjukan artistik tetapi juga sebagai media untuk revitalisasi budaya dan transmisi nilai-nilai lokal antar generasi.